ZJAWISKO EDUKACJI TRANSGRANICZNEJ NA PRZYKŁADZIE UKRAIŃSKICH STUDENTÓW NA PODKARPACIU - Długosz, Piotr (My University, 2015)
The article presents the results of research on Ukrainian students studying in Podkarpacie region. In the research the survey method was used and answers from 250 students in Rzeszów and Przemyśl were received. The study shows that the main reasons for studying abroad were the desire to see the world, obtaining a diploma of a foreign university and the will to avoid corrupt practices. The main problems Ukrainian students have to face upon arriving at Poland include the cost of living, not knowing Polish and homesickness. The highest notes were given to university’s equipment, rapport with lecturers and administrative workers. On the other hand, city facilities and possibilities of spending free time were assessed lower. The lowest marks were given to economic conditions and possibilities of earning money during studies or upon graduating. Most of the students want to stay in Poland or leave for the West after graduating. A small group of respondents plans to return to Ukraine.
THE PHENOMEN OF CROSS-BORDER EDUCATION AS EXEMPLIFIED BY UKRAUNIAN STUDENTS IN PODKARPACIE REGION
Keywords: cross-border education; survey method; Ukrainian students; Podkarpacie; evaluation of studies; life plans